2007
DOI: 10.1177/1354068807080083
|View full text |Cite
|
Sign up to set email alerts
|

Duverger's Law and the Size of the Indian Party System

Abstract: Duverger's law postulates that single-member plurality electoral systems lead to two-party systems. Existing scholarship regards India as an exception to this law at national level, but not at district level. This study tests the latter hypothesis through analysis of a comprehensive dataset covering Indian parliamentary elections in the period 1952—2004. The results show that a large number of Indian districts do not conform to the Duvergerian norm of two-party competition, and that there is no consistent move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 23 publications
3
30
0
1
Order By: Relevance
“…Most of these studies have been concerned with single cases. Although using superior measures, some of these studies have still shown that Duverger's law lacks in empirical accuracy when looking at specific cases, such as Canada (Gaines, 1999), India (Diwakar, 2007) or the UK (Stephenson & Singer, 2011). Similarly, Moser (2001) has shown that the SMD districts in Russia's mixed electoral system produce rather non-duvergerian outcomes.…”
Section: Empirical Assessments Of Institutions and Coordinationmentioning
confidence: 98%
“…Most of these studies have been concerned with single cases. Although using superior measures, some of these studies have still shown that Duverger's law lacks in empirical accuracy when looking at specific cases, such as Canada (Gaines, 1999), India (Diwakar, 2007) or the UK (Stephenson & Singer, 2011). Similarly, Moser (2001) has shown that the SMD districts in Russia's mixed electoral system produce rather non-duvergerian outcomes.…”
Section: Empirical Assessments Of Institutions and Coordinationmentioning
confidence: 98%
“…The United Kingdom is just one example but similar conclusions can be drawn from considering election outcomes in Canada, India, and prereform New Zealand (cf. Chhibber and Kollman 1998;Gaines 1999;Cox and Schoppa 2002;Diwakar 2007;Grofman et al 2009). …”
Section: Introductionmentioning
confidence: 93%
“…2 Despite the strong equilibrium prediction, third party desertion is usually far from complete in actual mass elections. As a prime example, consider British parliamentary elections: 1 For empirical evidence on strategic voting, see, e.g., Cain (1978), Galbraith and Rae (1989), Johnston and Pattie (1991), Ordeshook and Zeng (1997), Blais et al (2005), Alvarez et al (2006), and for empirical evidence on the number of parties in single member constituencies being generally greater than two, see, e.g., Gaines (1999), Cox and Schoppa (2002), Diwakar (2007), Grofman et al (2009). 2 A second type of equilibrium arising from this literature is a so-called non-Duvergerian equilibrium; a state in which the two challengers obtain exactly the same number of votes (see Palfrey 1989;Cox 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Chhibber, Kollman 1998;Diwakar 2007). Z prac tych wynika, że tezy o łatwym do przewidzenia i zarazem pozytywnym wpły-wie implementacji JOW-ów w wyborach do Sejmu RP należy uznać za wątpliwe.…”
unclassified